2011
DOI: 10.1016/b978-0-12-387688-1.00006-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Techniques to Address Diversity in Tumors

Abstract: Array based genotyping platforms have during recent years been established as a valuable tool for the characterization of genomic alterations in cancer. The analysis of tumor samples, however, presents challenges for data analysis and interpretation. For example, tumor samples are often admixed with nonaberrant cells that define the tumor microenvironment, such as infiltrating lymphocytes and fibroblasts, or vasculature. Furthermore, tumors often comprise subclones harboring divergent aberrations that are acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…More generally, MATH will be straightforward to apply clinically in other types of cancer, for there is nothing specific to HNSCC in the underlying analysis of exome sequence data. Unlike approaches to measuring intra-tumor heterogeneity that require pre-identification of subclone markers [ 17 , 18 ], detailed analysis of SNP arrays [ 26 , 50 ], or analysis of multiple portions down to single cells of a tumor [ 13 , 20 , 22 , 25 ], MATH calculations require no information beyond a list of tumor-specific mutations and their MAFs, derived directly from a patient’s tumor and normal DNA. Thus, as WES enters the practice of clinical oncology [ 8 , 32 ], MATH will provide a novel and straightforward way to incorporate information about intra-tumor heterogeneity into clinical research and practice.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, MATH will be straightforward to apply clinically in other types of cancer, for there is nothing specific to HNSCC in the underlying analysis of exome sequence data. Unlike approaches to measuring intra-tumor heterogeneity that require pre-identification of subclone markers [ 17 , 18 ], detailed analysis of SNP arrays [ 26 , 50 ], or analysis of multiple portions down to single cells of a tumor [ 13 , 20 , 22 , 25 ], MATH calculations require no information beyond a list of tumor-specific mutations and their MAFs, derived directly from a patient’s tumor and normal DNA. Thus, as WES enters the practice of clinical oncology [ 8 , 32 ], MATH will provide a novel and straightforward way to incorporate information about intra-tumor heterogeneity into clinical research and practice.…”
Section: Discussionmentioning
confidence: 99%
“…It provides a stark contrast to current strategies for biomarker evaluation, with mutation status, genome profile or protein expression typically being evaluated in merely a single tumour sample-resting on the assumption that tumours are biologically homogeneous 5 . Microdiversity would be a particularly attractive clinical marker as it is a parameter possible to quantify using standard genome arrays and relatively simple bioinformatic operations 17 . The fact that we found a potential prognostic value of microdiversity in preoperatively treated nephroblastoma may be of particular interest because there is currently no standard molecular prognosticator for the many children worldwide treated for nephroblastoma under protocols with mandatory preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer cell fraction ranged from 60 to 99%, well in agreement with clearly deviant SNP array profiles, which fulfilled local criteria for clinical analysis ( Supplementary Figs 8-11). The method for estimating the proportion of cells containing a certain allelic imbalance from Illumina arrays has previously been validated by us and others 9,17,35,36 . In brief, the fraction of cells within single tumour samples that harboured each detected allelic imbalance was calculated using mirrored B-allele frequency (mBAF) values from the BAF-segmentation algorithm for Illumina arrays 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of clonal karyotypic heterogeneity has been documented for several tumor types, and cytogenetic investigations have revealed coexisting related but divergent subclones in several tumor types. In addition, comparative genome hybridization analyses have indicated an underlying heterogeneity with respect to copy number alterations and to the presence of subclones with different sets of genomic alterations [1]. Furthermore, investigations based on the sequencing of more than one gene in the same biopsy revealed that some mutations are present in all tumor cells, whereas others are not.…”
mentioning
confidence: 98%